Science Education Research and New Technologies - Vanderlei Dos Santos, Antonio; Carlos Krause, Joao (IntechOpen, 2017)
The book presents a discussion on education of sciences, through a technological view shown in the works of a variety of authors from different countries. It's a differentiated conception of scientific education bringing renowned authors who discuss from teacher formation to the inclusion of new technologies into education. We are proud to say that the themes discussed in the book are up to date and also of scientific interest in many countries, as seen by the collaborating authors who come from many parts of the world. The scientific discussion becomes evident through the effort of the authors in participating in this book that will serve as a reference for future research for those who want to develop modern educational approaches.